Utilization of Outpatient Eye Care Services in Taiwan: A Nationwide Population Study - Chia-An Hsu; Sheng-Huang Hsiao; Min-Huei Hsu; Ju-Chuan Yen (Journal of Ophthalmology)
Introduction. A study based on the Taiwanese National Health Insurance Research Database (NHIRD) to reveal the ocular diseases landscape. Materials and Methods. This study comprised all ophthalmological outpatient patient visits (n = 6,341,266) in the Taiwanese longitudinal NHIRD 2000. Descriptive analytics based on 15 disease categories of ICD-9-CM and 10 tiers of age categories was performed with SAS for Windows 9.3 (SAS Institute, Inc., Cary, NC, U.S.A.). Results. The average frequency of visits was 0.7 visits per year. The mean age was 36.2 years old. Bimodal peak of visits in the first, second, and eighth decade of life was revealed. Conjunctiva is the most dominant disease category throughout life while different categories play major roles in each decade of life. The most frequent disease code of each category was listed. Discussion. The bimodal peak of visits revealed the age group of the most prominent ocular disease burden. Peak in school age population can be partially explained by the nationwide vision screening program, while aging accounts for the lens disorder and glaucoma of the senile peak. The disease category frequency variation among age categories reflects the development and aging of the eye. The most frequent disease codes of each category highlight disease of importance for primary practitioners and ophthalmologists. Conclusion. Taiwanese longitudinal NHIRD was used to reveal the ophthalmological disease landscape. The epidemiological insight, while limited in clinical presentation and economic impact, enables physicians and policy makers to improve the overall vision health of the population.